Modified vinasse as well as preparation method and application thereof

By using coupling agent and hyperbranched resin in the lees powder for chemical reaction, the lees powder is modified to improve compatibility with biodegradable resin, and the problem of poor interface compatibility between the lees and resin is solved, achieving high-performance biological The preparation of degraded composite materials and the efficient use of wine lees have solved the problems of resource waste and environmental pollution.

CN119192874AActive Publication Date: 2024-12-27GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411574583.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-27
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize the winemaking by-product wine lees, which leads to waste of resources and environmental pollution. The wine lees have poor compatibility with biodegradable resins, resulting in poor performance of composite materials.

Method used

Use coupling agent and hyperbranched resin to undergo chemical reaction with the lees powder. Through synergistic effect, the lees powder is modified to improve its compatibility with biodegradable resin and interface bond strength, and the modified lees are prepared and used for preparation. Fully biodegradable green composite material.

Benefits of technology

It improves the compatibility and performance of composite materials, realizes the high-value utilization of wine lees, extends its application areas, ensures the biodegradability and environmental protection of the materials, and improves production efficiency and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_11
    Figure SMS_11
  • Figure SMS_12
    Figure SMS_12
  • Figure SMS_13
    Figure SMS_13
Patent Text Reader

Abstract

The invention belongs to the field of composite material preparation, and particularly relates to modified vinasse as well as a preparation method and application thereof. Coupling agents with different reactive groups are matched with hyperbranched resin with different reactive end groups at the tail end, and the surface of the vinasse powder is regulated and controlled through the synergistic effect of the coupling agents and the hyperbranched resin, so that the problems of poor interfacial compatibility of the vinasse powder and biodegradable resin and agglomeration caused by strong hydrogen-bond interaction between the vinasse powder are solved; the compatibility and the interface bonding strength of the vinasse powder and the biodegradable resin are improved, and the full-biodegradable green composite material with excellent performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite material preparation, and particularly relates to modified distiller's grains and a preparation method and application thereof. Background Art

[0002] Green composite materials are a type of composite materials that use renewable biomass resources as raw materials, and at least one of the component materials is obtained from natural resources and can be completely degraded. In recent years, with the increasing shortage of petrochemical polymer materials and their composite materials and the strengthening of environmental protection requirements, the demand for green and environmentally friendly materials has also increased. As a type of green and environmentally friendly material, biodegradable composite materials prepared with natural biomass fillers have received widespread attention in the market. In the past few years, researchers have successfully prepared green composite materials using a variety of biomass fillers such as rice husk powder, bamboo powder, cellulose, and lignin. Biomass fillers have become one of the most popular fillers due to their rich sources and natural biodegradability.

[0003] Wine lees are solid wastes obtained after wheat, sorghum and other grains are cooked, fermented and distilled to produce wine. The output is huge. Wine lees have high water content, high acidity and are easy to rot and deteriorate. Improper treatment will seriously pollute the ecological environment. It is imperative to reduce the amount of wine lees, make them harmless and recycle them as resources.

[0004] Studies have shown that distiller's grains are rich in hemicellulose and lignin, which can be used as biomass fillers to further reduce the cost of composite materials, and have received continuous attention in recent years. In addition to cellulose and lignin, distiller's grains also contain rich nutrients and various active functional ingredients, including alcohols, acids, aldehydes, esters, proteins, amino acids, active peptides, functional oligosaccharides, antioxidant phenols and flavonoids. They have high utilization value and huge development potential, and are an important resource. It is urgent to promote the resource utilization of distiller's grains, turn waste into treasure, and achieve green and circular development, and to carry out research on the high-value utilization of distiller's grains. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing modified distiller's grains, comprising the steps of:

[0006] (1) crushing and drying the vinasse, grinding and sieving to obtain vinasse powder;

[0007] (2) adding a coupling agent to the vinasse powder, heating and stirring, and obtaining coupling agent treated vinasse;

[0008] (3) Adding a hyperbranched resin to the coupling agent treated wine lees, heating and stirring for 5 to 45 minutes, and cooling to room temperature after the heating and stirring are completed to obtain modified wine lees.

[0009] Furthermore, the drying temperature in step (1) is 80-120° C.; and the particle size of the vinasse powder is 100-2000 mesh.

[0010] Furthermore, the coupling agent in step (2) is selected from at least one of a silane coupling agent, an aluminate coupling agent and a titanate coupling agent; and the weight ratio of the vinasse powder to the coupling agent is 10:1 to 300:1.

[0011] Furthermore, the silane coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane; and the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.

[0012] Furthermore, the hyperbranched resin in step (3) is selected from at least one of amino-terminated hyperbranched polyester, carboxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyester, hyperbranched epoxy resin, hydroxyl-terminated hyperbranched polyamide and amino-terminated hyperbranched polyamide; and the weight ratio of lees powder to hyperbranched resin is 5:1 to 300:1.

[0013] The present invention also provides a green composite material of fully biodegradable distiller's grains, which comprises 5-95wt% of biodegradable polyester, 0.1-15wt% of chain extender, 1-75wt% of modified distiller's grains, 0.1-15wt% of anti-hydrolysis agent, 0.1-5wt% of heat stabilizer and 0.1-7.5wt% of lubricant; the modified distiller's grains are prepared by the above-mentioned preparation method.

[0014] Furthermore, the biodegradable polyester is selected from at least one of polybutylene adipate / terephthalate copolyester, polylactic acid, polybutylene succinate, polybutylene succinate / adipate, polymethyl acetyl carbonate, polyglycolide, polyε-caprolactone, polyhydroxyalkanoate, polyhydroxybutyrate, polyhydroxyvalerate, and polyhydroxybutyrate / valerate; the chain extender is selected from at least one of epoxy compound chain extenders and styrene-methylacrylate copolymer chain extenders; the anti-hydrolysis agent is selected from at least one of carbodiimide compounds, isocyanate compounds, bisoxazoline compounds, and epoxy compounds; the heat stabilizer is selected from at least one of aromatic amine compounds, hindered phenol compounds, phosphite compounds, and thioester compounds; the lubricant is selected from at least one of long-chain carboxylic acids, amide waxes, carboxylates, carboxylates, and silicone resins.

[0015] The present invention also provides a method for preparing the above-mentioned wine lees fully biodegradable green composite material, the steps comprising: mixing biodegradable polyester, chain extender, anti-hydrolysis agent, heat stabilizer and lubricant to obtain a biodegradable polyester material mixture; mixing the biodegradable polyester material mixture with modified wine lees, and fully drying after mixing to obtain a wine lees fully biodegradable green composite material.

[0016] The present invention also provides the use of the above-mentioned wine lees fully biodegradable green composite material as a material for film blowing, injection molding, casting, rotational molding, 3D printing, extrusion, laminating, spinning, vacuum forming and molding.

[0017] The present invention has the following beneficial effects:

[0018] (1) The present invention provides a large-scale and high-value utilization of wine lees, a byproduct of brewing. The present invention selects coupling agents with different reactive groups to react chemically with reactive groups carried by wine lees, hyperbranched resins and biodegradable resins; the present invention selects hyperbranched resins with different terminal reaction groups to match different types of coupling agents, and through the synergistic effect of the coupling agent and the hyperbranched resin, the surface of the wine lees powder is modified and regulated, solving the problem of poor interface compatibility between wine lees powder and biodegradable resins and the strong hydrogen bonding between wine lees powder molecules leading to their agglomeration and thus poor performance, improving the compatibility and interface bonding strength between wine lees and biodegradable resins, and obtaining a biodegradable green composite material with excellent performance.

[0019] (2) The composite material provided by the present invention increases the filling amount of the composite material's vinasse powder while meeting the product standards and performance, thereby expanding the application field of vinasse biodegradable green composite materials, thereby accelerating the consumption of vinasse, avoiding waste of resources and serious environmental pollution, and bringing social and ecological benefits while bringing certain economic benefits.

[0020] (3) The matrix resins used in the present invention are all fully biodegradable resins, and the vinasse is also added as a green bio-based filler into the biodegradable resin to obtain a composite material that is completely biodegradable within a certain environment and date, truly achieving the reduction, harmlessness, and resource utilization of vinasse.

[0021] (4) The processing technology of total distiller's grains powder and the preparation technology of green fully biodegradable composite materials of the present invention are convenient and feasible, with high production efficiency and high economic benefits, and have great prospects for industrial application. DETAILED DESCRIPTION

[0022] Now, various exemplary embodiments of the present invention are described in detail. The methods in the examples are conventional methods unless otherwise specified, and the reagents used are conventional commercially available reagents or reagents prepared by conventional methods unless otherwise specified. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] Unless otherwise specified, the raw materials used in the examples are all commercially available products.

[0028] PBAT resin, TH801T, was purchased from Xinjiang Blue Mountain Tunhe Technology Co., Ltd.;

[0029] PLA resin, LX175, purchased from TotalEnergies Corbion;

[0030] PPC resin, T4, purchased from Jiangsu Zhongke Jinlong Chemical Co., Ltd.;

[0031] PBS resin, FZ71PM, was purchased from PTT MCC Biochem Company Limited;

[0032] PBSA resin, FD92PB, was purchased from PTT MCC Biochem Company Limited;

[0033] PHBV resin, Y1000, was purchased from Ningbo Tianan Biomaterials Co., Ltd.;

[0034] PGA resin, G 205S, purchased from Evonik;

[0035] PCL resin, Esun 1000C, was purchased from Shenzhen Guanghua Weiye Co., Ltd.

[0036] The coupling agents γ-aminopropyltriethoxysilane (KH-550), (KH-560) and isopropyl tri(dioctylpyrophosphate) titanate (NDZ-201) were purchased from Nanjing Shuguang Chemical Group Co., Ltd.

[0037] Embodiment 1:

[0038] Preparation of modified vinasse: (1) After white wine vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the water; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000 rad / min, and the mixture is heated to 100°C; under high-speed stirring, coupling agent KH560 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 50:1, and after the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes to obtain KH560 treated vinasse powder. (2) Then, the carboxyl-terminated hyperbranched polyester Hyper C304 was added to the vinasse powder treated with the above KH560 according to the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1, the speed of the high-speed mixer was set to 1000 rad / min, the material temperature was controlled at 100° C., and the mixture was stirred for 30 min; after the reaction was completed, the heating was stopped, the mixture was stirred at a low speed of 100 r / min, and the mixture was cooled to room temperature to obtain KH560 and Hyper C304 combined modified vinasse 1#, which was set aside.

[0039] Preparation of green composite materials made of fully biodegradable distillers' grains: (1) placing biodegradable polyesters PBAT and PLA in drying equipment for full drying; ADR 4468 (0.8wt%), anti-hydrolysis agent polymeric carbodiimide (1.6wt%), thermal stabilizer 1010 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant erucamide (0.2wt%) were weighed according to the above weight percentage and added into a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 1000rad / min, and the mixing time was set to 10min; and the mixture 1# was obtained. (2) The mixture 1# and modified distiller's grains 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 1# (wt%): modified distiller's grains 1# (wt%) = 80:20. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain distiller's grains fully biodegradable green composite material 1#; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0040] Embodiment 2:

[0041] Preparation of modified distiller's grains: same as in Example 1.

[0042] Preparation of green composite materials made of fully biodegradable distillers' grains: (1) placing biodegradable polyesters PBAT and PLA in drying equipment for full drying; ADR 4468 (0.7wt%), anti-hydrolysis agent polymeric carbodiimide (1.4wt%), thermal stabilizer 1010 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant erucamide (0.3wt%) were weighed according to the above weight percentage and added to the high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was 1000rad / min, and the mixing time was 10min; the mixture 2# was obtained. (2) The mixture 2# and modified wine lees 1# obtained above were placed in the funnels of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 2# (wt%): modified wine lees 1# (wt%) = 70:30. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain wine lees fully biodegradable green composite material 2#; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0043] Embodiment 3:

[0044] Preparation of modified distiller's grains: same as in Example 1.

[0045] Preparation of fully biodegradable green composite materials from wine lees: (1) placing biodegradable polyesters PBAT and PLA in drying equipment for full drying; ADR 4468 (0.6wt%), hydrolysis-resistant polymeric carbodiimide (1.2wt%), thermal stabilizer 1010 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant erucamide (0.4wt%) were weighed according to the above weight percentage and added to a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 1000rad / min, and the mixing time was set to 10min; and a mixture 3# was obtained. (2) The mixture 3# and modified wine lees 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 3# (wt%): modified wine lees 1# (wt%) = 60:40. After extrusion, stranding, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain wine lees fully biodegradable green composite material 3#; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0046] Embodiment 4:

[0047] Preparation of modified distiller's grains: same as in Example 1.

[0048] Preparation of green composite materials made of fully biodegradable distillers' grains: (1) placing biodegradable polyesters PBAT and PLA in drying equipment for full drying; ADR 4468 (0.5wt%), hydrolysis-resistant polymeric carbodiimide (1.0wt%), thermal stabilizer 1010 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant erucamide (0.5wt%) were weighed according to the above weight percentage and added to a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 1000rad / min, and the mixing time was set to 10min; and a mixture 4# was obtained. (2) The mixture 4# and modified wine lees 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 4# (wt%): modified wine lees 1# (wt%) = 50:50. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain wine lees fully biodegradable green composite material 4#; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0049] Embodiment 5:

[0050] Preparation of modified vinasse: (1) The vinasse treated with coupling agent is the same as in Example 1, and vinasse powder treated with KH560 is obtained. (2) Then, the carboxyl-terminated hyperbranched polyester Hyper C181 is added to the vinasse powder treated with the coupling agent KH560 at a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1, the speed of the high-speed mixer is set to 1000 rad / min, the material temperature is controlled at 100°C, and stirring is carried out for 30 minutes; after the reaction is completed, heating is stopped, stirring is carried out at a low speed of 100 r / min, and cooling is carried out to room temperature to obtain KH560 and Hyper C181 combined modified vinasse 2#, which is set aside.

[0051] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 2# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 5# (wt%): modified wine lees 2# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 5#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0052] Embodiment 6:

[0053] Preparation of modified vinasse: (1) After the white wine vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the water; the fully dried white wine vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000 rad / min, and the mixture is heated to 100°C; under high-speed stirring, coupling agent KH550 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 50:1, and after the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes to obtain vinasse powder treated with coupling agent KH550. (2) Then, according to the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1, the hyperbranched epoxy resin Hyper E102 was added to the vinasse powder treated with the coupling agent KH550, the speed of the high-speed mixer was set to 1000 rad / min, the material temperature was controlled at 100°C, and the mixture was stirred for 30 minutes; after the reaction was completed, the heating was stopped, the mixture was stirred at a low speed of 100 r / min, and the mixture was cooled to room temperature to obtain KH550 and Hyper E102 combined modified vinasse 3#, which was set aside.

[0054] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 3# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 6# (wt%): modified wine lees 3# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 6#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0055] Embodiment 7:

[0056] Preparation of modified vinasse: (1) crushing liquor vinasse, washing it thoroughly in water, filtering the water and drying it in a drying oven at 100°C; grinding and sieving the thoroughly dried liquor vinasse in a grinder to a particle size of 1250 mesh to obtain vinasse powder; adding the vinasse powder to a high-speed mixer, setting the speed to 1000 rad / min, and heating to 100°C; under high-speed stirring, adding coupling agent NDZ-201 in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 50:1 while stirring, and after the addition is completed, controlling the material temperature to 100°C and stirring for 30 minutes to obtain vinasse powder treated with coupling agent NDZ-201. (2) Then, add the carboxyl-terminated hyperbranched polyester Hyper C304 to the vinasse powder treated with the coupling agent NDZ-201 according to the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1, set the speed of the high-speed mixer to 1000 rad / min, control the material temperature at 100°C, and stir for 30 minutes; after the reaction is completed, stop heating, stir at a low speed of 100 r / min, and cool to room temperature to obtain NDZ-201 and Hyper C304 combined modified vinasse 4#, which is set aside.

[0057] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 4# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 7# (wt%): modified wine lees 4# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 7#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0058] Embodiment 8:

[0059] Preparation of modified vinasse: (1) The vinasse treated with coupling agent is the same as in Example 7 to obtain vinasse powder treated with NDZ-201. (2) Then, Hyper C181 is added to the vinasse powder treated with the coupling agent NDZ-201 at a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1, the speed of the high-speed mixer is set to 1000 rad / min, the material temperature is controlled at 100°C, and stirred for 30 minutes; after the reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100 r / min, and the mixture is cooled to room temperature to obtain vinasse 5# jointly modified with NDZ-201 and Hyper C181, which is set aside.

[0060] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 5# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 8# (wt%): modified wine lees 5# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 8#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0061] Embodiment 9:

[0062] Preparation of wine modified lees: (1) The lees were treated with coupling agent as in Example 6 to obtain lees powder treated with KH550. (2) Then, the carboxyl-terminated hyperbranched polyester Hyper C304 was added to the lees powder treated with the coupling agent KH550 at a weight ratio of lees powder (wt%): hyperbranched resin (wt%) = 50:1, the speed of the high-speed mixer was set to 1000 rad / min, the material temperature was controlled at 100°C, and stirred for 30 minutes; after the reaction was completed, the heating was stopped, the mixture was stirred at a low speed of 100 r / min, and cooled to room temperature to obtain KH550 and Hyper C304 combined modified lees 6#, which was set aside.

[0063] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 6# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 9# (wt%): modified wine lees 6# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 9#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0064] Embodiment 10:

[0065] Preparation of modified vinasse: (1) The vinasse treated with coupling agent is the same as in Example 6, and vinasse powder treated with coupling agent KH550 is obtained. (2) Then, carboxyl-terminated hyperbranched polyester Hyper C181 is added to the vinasse powder treated with coupling agent KH550 at a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1, the speed of the high-speed mixer is set to 1000 rad / min, the material temperature is controlled at 100°C, and stirred for 30 minutes; after the reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100 r / min, and cooled to room temperature to obtain KH550 and Hyper C181 combined modified vinasse 7#, which is set aside.

[0066] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 7# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 7# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 10#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0067] Embodiment 11:

[0068] Preparation of modified lees: (1) Treatment of lees with coupling agent: Same as in Example 1. (2) Treatment of lees with hyperbranched resin: Then, amino-terminated hyperbranched polyester Amine Functional Boltorn was added to the lees powder treated with the coupling agent KH560 at a weight ratio of lees powder (wt%): hyperbranched resin (wt%) = 50:1. TM H40, set the high-speed mixer speed to 1000rad / min, control the material temperature at 100℃, and stir for 30min; after the reaction is completed, stop heating, stir at a low speed of 100r / min, and cool to room temperature to obtain KH560 and Amine Functional Boltorn TM H40 combined with modified distiller's grains 8#, for standby use.

[0069] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 8# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 8# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 11#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0070] Embodiment 12:

[0071] Preparation of modified vinasse: (1) The vinasse treated with coupling agent is the same as in Example 1 to obtain vinasse powder treated with KH560. (2) Then, the terminal hydroxyl hyperbranched polyester Boltorn is added to the vinasse powder treated with coupling agent KH560 according to the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1. TM Regular H40, set the high-speed mixer speed to 1000rad / min, control the material temperature at 100℃, and stir for 30min; after the reaction is completed, stop heating, stir at a low speed of 100r / min, and cool to room temperature to obtain KH560 and Boltorn TM Regular H40 combined with modified distiller's grains 9#, for standby use.

[0072] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 9# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 9# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 12#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0073] Embodiment 13:

[0074] Preparation of modified vinasse: (1) After the white wine vinasse is crushed, it is fully washed in water, filtered and placed in a drying oven at 80°C to dry the water; the fully dried white wine vinasse is placed in a grinder and ground and sieved to a particle size of 100 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 2000 rad / min, and the mixture is heated to 90°C; under high-speed stirring, coupling agent KH560 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 100:1, and after the addition is completed, the material temperature is controlled at 90°C and stirred for 5 minutes to obtain vinasse powder treated with coupling agent KH560. (2) Then, add the terminal hydroxyl hyperbranched polyester Hyper H304 to the vinasse powder treated with the coupling agent KH560 according to the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 25:1, set the speed of the high-speed mixer to 100 rad / min, control the material temperature at 90°C, and stir for 45 minutes; after the reaction is completed, stop heating, stir at a low speed of 100 r / min, and cool to room temperature to obtain KH560 and Hyper H304 combined modified vinasse 10#, which is set aside.

[0075] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 11# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 11# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 13#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0076] Embodiment 14:

[0077] Preparation of modified vinasse: (1) After the white wine vinasse is crushed, it is fully washed in water, filtered and placed in a 120°C drying oven to dry the water; the fully dried white wine vinasse is placed in a grinder and ground and sieved to a particle size of 2000 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 100 rad / min, and the mixture is heated to 110°C; under high-speed stirring, the coupling agent NDZ-201 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 25:1, and after the addition is completed, the material temperature is controlled to 110°C and stirred for 45 minutes to obtain vinasse powder treated with coupling agent NDZ-201. (2) Then, add hyperbranched epoxy resin Hyper E102 to the vinasse powder treated with the coupling agent NDZ-201 according to the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 100:1, set the speed of the high-speed mixer to 2000 rad / min, control the material temperature at 110°C, and stir for 5 minutes; after the reaction is completed, stop heating, stir at a low speed of 100 r / min, and cool to room temperature to obtain NDZ-201 and HyperH304 combined modified vinasse 11#, which is set aside.

[0078] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 11# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 11# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 14#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0079] Embodiment 15:

[0080] Preparation of modified distiller's grains: The only difference from Example 1 is that the distiller's grains used in this example are beer distiller's grains, and the remaining products and processes used are the same as those in Example 1, obtaining modified distiller's grains 12#.

[0081] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 12# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 12# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 15#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0082] Embodiment 16:

[0083] Preparation of modified distiller's grains: The only difference from Example 1 is that the distiller's grains used in this example are rice wine distiller's grains, and the remaining products and processes used are the same as those in Example 1, obtaining modified distiller's grains 13#.

[0084] Preparation of fully biodegradable green composite material of wine lees: Mixture 2# and modified wine lees 13# are placed in the funnels of different automatic loss-in-weight feeders respectively, and the feeding parameters are set according to the ratio requirement of mixture 2# (wt%): modified wine lees 13# (wt%) = 70:30. After extrusion, pulling, cooling and granulation by a twin-screw extruder, the obtained pellets are fully dried to obtain wine lees fully biodegradable green composite material 16#; during the processing, the extruder temperature is set to 180°C and the main engine speed is 300rpm.

[0085] Embodiment 17:

[0086] Preparation of modified distiller's grains: As in Example 1, obtain modified distiller's grains 1# for later use.

[0087] Preparation of green composite materials of wine lees biodegradable: (1) placing biodegradable polyester PPC in a drying device for full drying; 4468 (0.7wt%), hydrolysis-resistant monomeric carbodiimide (1.0wt%), thermal stabilizer 1076 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant palmitic acid (0.3wt%) were weighed according to the above weight percentage and added into a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 1000rad / min, and the mixing time was set to 10min; and a mixture 5# was obtained. (2) The mixture 5# and modified wine lees 1# obtained above were placed in the funnels of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 5# (wt%): modified wine lees 1# (wt%) = 70:30. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain wine lees fully biodegradable green composite material 17#; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0088] Embodiment 18:

[0089] Preparation of modified distiller's grains: As in Example 1, obtain modified distiller's grains 1# for later use.

[0090] Preparation of green composite materials made of fully biodegradable distillers grains: (1) placing biodegradable polyester PBS in a drying device for full drying; TM HPC-3510P (0.7wt%), hydrolysis-resistant monomeric carbodiimide (1.0wt%), thermal stabilizer 330 (0.2wt%), thermal stabilizer 636 (0.2wt%) and lubricant montanic acid (0.3wt%) were weighed according to the above weight percentage and added to a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 1000rad / min, and the mixing time was set to 10min; and a mixture 6# was obtained. (2) The mixture 6# and modified vinasse 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 6# (wt%): modified vinasse 1# (wt%) = 70:30. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain vinasse fully biodegradable green composite material 18#; during the processing, the extruder temperature was set to 135°C and the main engine speed was 300rpm.

[0091] Embodiment 19:

[0092] Preparation of modified distiller's grains: As in Example 1, obtain modified distiller's grains 1# for later use.

[0093] Preparation of green composite materials of wine lees biodegradable: (1) placing biodegradable polyester PHBV in a drying device for full drying; 4400 (0.7wt%), anti-hydrolysis monomeric carbodiimide (0.1wt%), thermal stabilizer 1098 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant stearic acid pentaerythritol (0.3wt%) were weighed according to the above weight percentage and added into a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 1000rad / min, and the mixing time was set to 10min; and a mixture 6# was obtained. (2) The mixture 6# and modified wine lees 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 6# (wt%): modified wine lees 1# (wt%) = 65:35. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain wine lees fully biodegradable green composite material 19#; during the processing, the extruder temperature was set to 200°C and the main engine speed was 300rpm.

[0094] Embodiment 20:

[0095] Preparation of modified distiller's grains: As in Example 1, obtain modified distiller's grains 1# for later use.

[0096] Preparation of green composite materials of wine lees biodegradable: (1) placing biodegradable polyester PGA in a drying device for full drying; 4440 (5.05wt%), hydrolysis-resistant monomeric carbodiimide (3.3wt%), thermal stabilizer 245 (1wt%), thermal stabilizer 626 (0.55wt%) and lubricant zinc stearate (0.1wt%) were weighed according to the above weight percentage and added into a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 100rad / min, and the mixing time was set to 15min; and a mixture 6# was obtained. (2) The mixture 6# and modified distiller's grains 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 6# (wt%): modified distiller's grains 1# (wt%) = 95:5. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain distiller's grains fully biodegradable green composite material 20#; during the processing, the extruder temperature was set to 250°C and the main engine speed was 100rpm.

[0097] Embodiment 21:

[0098] Preparation of modified distiller's grains: As in Example 1, obtain modified distiller's grains 1# for later use.

[0099] Preparation of green composite materials made of fully biodegradable distillers grains: (1) placing biodegradable polyester PCL in a drying device for full drying; TM ECO-1120 (2.3wt%), hydrolysis-resistant monomeric carbodiimide (5.05wt%), thermal stabilizer DPT (0.05wt%), thermal stabilizer 1790 (0.05wt%) and lubricant polysiloxane (2.55wt%) were weighed according to the above weight percentage and added into a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was set to 2000rad / min, and the mixing time was set to 5min; and a mixture 6# was obtained. (2) The mixture 6# and modified wine lees 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 6# (wt%): modified wine lees 1# (wt%) = 35:65. After extrusion, drawing, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain wine lees fully biodegradable green composite material 21#; during the processing, the extruder temperature was set to 100°C and the main engine speed was 400rpm.

[0100] Embodiment 22:

[0101] Preparation of modified distiller's grains: As in Example 1, obtain modified distiller's grains 1# for later use.

[0102] Preparation of fully biodegradable green composite materials from wine lees: (1) placing biodegradable polyester PBAT in a drying device for full drying; TM SG-20 (10wt%), anti-hydrolysis polymerizable carbodiimide (10wt%), thermal stabilizer 5067 (1.5wt%), thermal stabilizer 168 (1.5wt%) and lubricant stearic acid (5wt%) were weighed according to the above weight percentage and added to a high-speed mixer. The temperature of the high-speed mixer was set to room temperature, the speed was set to 1050rad / min, and the mixing time was set to 10min; a mixture 10# was obtained. (2) The mixture 10# and modified distiller's grains 1# obtained above were placed in the hoppers of different automatic loss-in-weight feeders, and the feeding parameters were set according to the ratio of mixture 10# (wt%): modified distiller's grains 1# (wt%) = 83:17. After extrusion, stranding, cooling and granulation by a twin-screw extruder, the obtained pellets were fully dried to obtain distiller's grains fully biodegradable green composite material 22#; during the processing, the extruder temperature was set to 180°C and the main engine speed was 250rpm.

[0103] Comparative Example 1:

[0104] The biodegradable polyester PBAT and PLA were placed in a drying device for full drying; the fully dried PBAT (68.04wt%) and PLA (0.7wt%), chain extender ADR 4468 (0.8wt%), anti-hydrolysis agent polymeric carbodiimide (1.4wt%), thermal stabilizer 1010 (0.2wt%), thermal stabilizer 168 (0.2wt%) and lubricant erucamide (0.3wt%) were weighed according to the above weight percentage and added to a high-speed mixer, and the temperature of the high-speed mixer was set to room temperature, the speed was 1000rad / min, and the mixing time was 10min; a mixed material was obtained. The obtained mixed material was placed in the funnel of an automatic loss-in-weight feeder, and the feeding parameters were set. The material required for comparative example 1 was prepared using a co-rotating twin-screw extruder, and the obtained pellets were fully dried after extrusion, drawing, cooling and granulation by the twin-screw extruder to obtain the material required for comparative example 1, which was marked as composite material A. During the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0105] Comparative Example 2:

[0106] Preparation of modified distiller's grains: After the liquor distiller's grains are crushed, they are fully washed in water, filtered and placed in a drying oven at 100°C to dry the moisture; the dried distiller's grains are placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain distiller's grains powder, which is marked as modified distiller's grains B.

[0107] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains B were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains B (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain composite material B; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0108] Comparative Example 3:

[0109] Preparation of modified vinasse: After the liquor vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the moisture; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000rad / min, and heated to 100°C; under high-speed stirring, the coupling agent KH560 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 25:1. After the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes. After the late reaction is completed, the heating is stopped, and the mixture is stirred at a low speed of 100r / min and cooled to room temperature to obtain KH560-treated vinasse powder, which is marked as modified vinasse C.

[0110] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains C were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains C (wt%) = 70:30, and the obtained pellets were fully dried after extrusion, stranding, cooling and granulation by a twin-screw extruder; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0111] Comparative Example 4:

[0112] Preparation of modified vinasse: After the liquor vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the moisture; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000rad / min, and the mixture is heated to 100°C; under high-speed stirring, the coupling agent KH550 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 25:1. After the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes. After the late reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100r / min, and the mixture is cooled to room temperature to obtain KH550-treated vinasse powder, which is marked as modified vinasse D.

[0113] Preparation of composite material: (1) Same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains D were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains D (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain composite material D; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0114] Comparative Example 5:

[0115] Preparation of modified vinasse: After the liquor vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the moisture; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000rad / min, and the mixture is heated to 100°C; under high-speed stirring, the coupling agent NDZ-201 is added while stirring in a weight ratio of vinasse powder (wt%): coupling agent (wt%) = 25:1. After the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes. After the late reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100r / min, and the mixture is cooled to room temperature to obtain KH550 treated vinasse powder, which is marked as modified vinasse E.

[0116] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains E were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains E (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain composite material E; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0117] Comparative Example 6:

[0118] Preparation of modified vinasse: After the liquor vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the moisture; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000rad / min, and the mixture is heated to 100°C; under high-speed stirring, the carboxyl-terminated hyperbranched polyester Hyper C304 is added while stirring in a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 25:1, and after the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes. After the late reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100r / min, and the mixture is cooled to room temperature to obtain Hyper C304-treated vinasse powder, which is marked as modified vinasse F.

[0119] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains F were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains F (wt%) = 70:30, and the obtained pellets were fully dried after extrusion, stranding, cooling and granulation by a twin-screw extruder; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0120] Comparative Example 7:

[0121] Preparation of modified vinasse: After the liquor vinasse is crushed, it is fully washed in water, filtered and placed in a 100°C drying oven to dry the moisture; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000rad / min, and the mixture is heated to 100°C; under high-speed stirring, a hyperbranched epoxy resin Hyper E102 is added while stirring in a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 25:1, and after the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes. After the late reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100r / min, and the mixture is cooled to room temperature to obtain Hyper E102-treated vinasse powder, which is marked as modified vinasse G.

[0122] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains G were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains G (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain composite material G; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0123] Comparative Example 8:

[0124] Preparation of modified vinasse: After the liquor vinasse is crushed, it is fully washed in water, filtered and placed in a drying oven at 100°C to dry the moisture; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000rad / min, and the mixture is heated to 100°C; under high-speed stirring, the carboxyl-terminated hyperbranched polyester Hyper C181 is added while stirring in a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 25:1, and after the addition is completed, the material temperature is controlled at 100°C and stirred for 30 minutes. After the late reaction is completed, the heating is stopped, the mixture is stirred at a low speed of 100r / min, and the mixture is cooled to room temperature to obtain Hyper C181-treated vinasse powder, which is marked as modified vinasse H.

[0125] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains H were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains H (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain composite material H; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0126] Comparative Example 9:

[0127] Preparation of modified wine lees: After white wine lees are crushed, they are fully washed in water, filtered and placed in a drying oven at 100°C to dry the water; the dried wine lees are placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain wine lees powder; the wine lees powder is added to a high-speed mixer, the speed is set to 1000 rad / min, and the mixture is heated to 100°C; under high-speed stirring, the amino-terminated hyperbranched polyester Amine Functional Boltorn is added in a weight ratio of wine lees powder (wt%): hyperbranched resin (wt%) = 25:1 while stirring. TM After adding H40, the material temperature was controlled at 100°C and stirred for 30 minutes. After the late reaction was completed, the heating was stopped, and the mixture was stirred at a low speed of 100 r / min and cooled to room temperature to obtain Amine Functional Boltorn. TM H40 treated distiller's grains powder, labeled as modified distiller's grains I.

[0128] Preparation of composite materials: (1) The same as Example 2, to obtain mixed material 2#. (2) Mixed material 2# and modified distiller's grains I were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of mixed material 2# (wt%): modified distiller's grains I (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain composite material I; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0129] Comparative Example 10:

[0130] Preparation of modified vinasse: After white wine vinasse is crushed, it is fully washed in water, filtered and placed in a drying oven at 100°C to dry the water; the dried vinasse is placed in a grinder and ground and sieved to a particle size of 1250 mesh to obtain vinasse powder; the vinasse powder is added to a high-speed mixer, the speed is set to 1000 rad / min, and the mixture is heated to 100°C; under high-speed stirring, the weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 25:1 is added while stirring. TM After the addition of Regular H40, the material temperature was controlled at 100°C and stirred for 30 minutes. After the late reaction was completed, the heating was stopped, and the mixture was stirred at a low speed of 100 r / min and cooled to room temperature to obtain Boltorn. TM Regular H40 processed distillers grains powder, marked as modified distillers grains J.

[0131] Preparation of composite materials: (1) The same as Example 2, to obtain a mixture 2#. (2) The mixture 2# and the modified distiller's grains J were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of the mixture 2# (wt%): modified distiller's grains J (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain a composite material J; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0132] Comparative Example 11:

[0133] Preparation of modified vinasse: (1) crushing liquor vinasse, washing it thoroughly in water, filtering the water and drying it in a drying oven at 100° C.; grinding and sieving the thoroughly dried liquor vinasse in a grinder to a particle size of 1250 mesh to obtain vinasse powder; adding the vinasse powder to a high-speed mixer, setting the speed to 1000 rad / min, and heating to 100° C.; under high-speed stirring, adding carboxyl-terminated hyperbranched polyester Hyper C304 in a weight ratio of vinasse powder (wt%): hyperbranched resin (wt%) = 50:1 while stirring, and after the addition is completed, controlling the material temperature to 100° C. and stirring for 30 minutes to obtain carboxyl-terminated hyperbranched polyester Hyper C304 modified vinasse powder. (2) Then, a coupling agent KH560 was added to the modified distiller's grains powder containing the above-mentioned terminal carboxyl hyperbranched polyester Hyper C304, with distiller's grains powder (wt%): coupling agent (wt%) = 50:1. The speed of the high-speed mixer was set to 1000 rad / min, the material temperature was controlled at 100° C., and stirring was carried out for 30 minutes. After the reaction was completed, heating was stopped, stirring was carried out at a low speed of 100 r / min, and cooling was carried out to room temperature to obtain Hyper C304 and KH560 combined modified distiller's grains, which were marked as modified distiller's grains K and set aside.

[0134] Preparation of composite materials: (1) The same as Example 2, to obtain a mixture 2#. (2) The mixture 2# and the modified distiller's grains I were placed in the hoppers of different automatic loss-in-weight feeders, respectively, and the feeding parameters were set according to the ratio of the mixture 2# (wt%): modified distiller's grains J (wt%) = 70:30, and the obtained pellets were extruded, stretched, cooled and granulated by a twin-screw extruder, and then fully dried to obtain a composite material K; during the processing, the extruder temperature was set to 180°C and the main engine speed was 300rpm.

[0135] In practical applications, when the wine lees fully biodegradable green composite material prepared by the present invention is used for film products, the film strength plays an important role in the packaging or handling of commodity goods. It ensures the integrity and availability of the film and has a strong guiding significance for various commodity applications. The purpose of the present invention is to propose a low-cost wine lees fully biodegradable green composite material with good mechanical properties. Therefore, all film samples were tensile tested by using a universal material testing machine to verify their mechanical properties. At the same time, the water vapor permeability of the film was tested to verify its barrier properties. The composite materials obtained in Examples 1-22 and Comparative Examples 1-11 of the present invention were prepared into films used for testing in the GB / T 35795-2017 standard, and their performance tests are listed in Table 1.

[0136] Table 1 Performance test results of Examples 1-22 and Comparative Examples 1-11

[0137]

[0138]

[0139]

[0140] (1) Analysis of test results of Comparative Example 1 and Examples 1-4:

[0141] Comparative Example 1 is a resin material without adding vinasse. It can be seen from Comparative Example 1 and Examples 1-4 that the tensile strength shows a trend of first increasing and then decreasing with the increase of the content of modified vinasse. In Example 2, when the content of modified vinasse is 30wt%, the tensile strength reaches the maximum value. Compared with Comparative Example 1, the transverse and longitudinal tensile strengths in Example 2 are increased by 142.3% and 151.16%, respectively; the elongation at break also shows a trend of first increasing and then decreasing with the content of modified vinasse. The reason for the increase in elongation at break is that the coupling agent and the hyperbranched resin serve as compatibilizers to increase the molecular chain length between the vinasse powder and the biodegradable resin matrix during the modification and blending of the vinasse powder, thereby forming a flexible interface and improving the elongation at break of the composite material. When the content of vinasse powder is too high, it may be due to poor agglomeration and dispersion of the vinasse powder. The elongation at break decreases; the water vapor permeability shows a trend of decreasing first and then increasing with the increase of the content of modified vinasse, and reaches the minimum value in Example 2; the following conclusions are drawn: ① Modified vinasse will increase the tensile strength of the composite material, but the tensile strength begins to decrease when the content of modified vinasse is 40% and 50%, and the increase in tensile strength is because the vinasse powder improves the interface strength with the biodegradable resin under the combined modification of coupling agent and hyperbranched polyester, thereby improving the strength; the reason why the strength decreases when the content of vinasse powder is further increased may be related to the partial agglomeration and uneven dispersion of excessive vinasse powder in the biodegradable polyester, but even so, the tensile strength of the composite material obtained with 40wt% (Example 3) and 50wt% (Example 3) modified vinasse content is higher than that of Comparative Example 1. Under the condition of meeting the use and strength requirements of the product, the content of vinasse powder can be increased to 50wt%, thereby providing data support for large-scale and rapid consumption of vinasse. ② The increase of modified lees will increase the elongation at break of the composite material, but too high lees powder content is not good for the elongation at break, which limits the places where higher elongation is required. ③ The water absorption rate will increase when the content of lees powder is high (50wt%), because lees powder is more hydrophilic than resin.

[0142] (2) Analysis of test results of Comparative Example 2 and Example 2:

[0143] The vinasse added in Comparative Example 2 was not treated with a coupling agent and a hyperbranched resin, while the vinasse powder in Example 2 was treated with a coupling agent KH560 and a carboxyl-terminated hyperbranched polyester Hyper C304. It can be seen from the test data that the transverse and longitudinal tensile strengths of Example 2 were increased by 82% and 74.9% respectively, and the transverse and longitudinal fracture productivity were increased by 71.7% and 73.9% respectively; the water absorption rate was increased from 931.8 g / (m 2 ·24h) decreased to 377.6g / (m 2·24h). It can be concluded that the wine lees treated with the coupling agent KH560 and the carboxyl-terminated hyperbranched polyester played a positive role in improving the performance of the composite material.

[0144] (3) Comparative analysis of the treatment of vinasse by coupling agent and hyperbranched resin and the treatment of vinasse by coupling agent or hyperbranched resin alone:

[0145] In Comparative Examples 3-5, the vinasse powder was treated with a coupling agent alone without a hyperbranched resin. Comparative Example 3 was treated with coupling agent KH560 alone, and compared with Examples 2, 5, 11, and 12; Comparative Example 4 was treated with coupling agent KH550 alone, and compared with Examples 6, 9, and 10; Comparative Example 5 was treated with coupling agent NDZ-201 alone, and compared with Examples 7 and 8.

[0146] In Comparative Examples 6-10, only hyperbranched resins were used to treat the lees powder without coupling agents. Comparative Example 6 was treated with only the carboxyl-terminated hyperbranched polyester Hyper C304, and compared with Examples 2, 7, and 9; Comparative Example 7 was treated with only the hyperbranched epoxy Hyper E102 and compared with Example 6; Comparative Example 8 was treated with only the carboxyl-terminated hyperbranched polyester Hyper C181, and compared with Examples 5, 8, and 10; Comparative Example 9 was treated with only the amino-terminated hyperbranched polyester Amine Functional Boltorn TM H40 and Example 11 are compared and analyzed; Comparative Example 10 uses only the terminal hydroxyl hyperbranched polyester Boltorn TM Regular H40 and Example 12 were compared and analyzed.

[0147] The following conclusions can be drawn from the test data of the above embodiments and comparative examples:

[0148] ① The performance of biodegradable polyester filled with wine lees powder treated with coupling agent alone or with hyperbranched resin alone is lower than that of the composite material obtained by treating wine lees powder with coupling agent and hyperbranched resin together; ② From comparative examples 3-5, it can be concluded that among coupling agents KH550, KH560H and NDZ-201, KH560H is better than the other two. ③ From comparative examples 6-9, it can be concluded that among carboxyl hyperbranched polyester Hyper C304, hyperbranched epoxy Hyper E102, carboxyl-terminated hyperbranched polyester Hyper C181, amino-terminated hyperbranched polyester Amine Functional Boltorn TM H40 and hydroxyl-terminated hyperbranched polyester Boltorn TMIn Regular H40, the treatment of carboxyl-terminated hyperbranched polyester Hyper C304 is better than the other four, but the performance of the biodegradable composite materials obtained by treating the five hyperbranched resins with wine lees is not much different. This is because wine lees powder not only contains a large number of hydroxyl groups, but also has rich active functional ingredients, including alcohols, acids, aldehydes, esters, proteins, amino acids, active peptides, functional oligosaccharides, antioxidant phenols and flavonoids. These active ingredients can react well with the terminal amino, terminal hydroxyl, terminal carboxyl and epoxy groups of the hyperbranched resin, so that the hyperbranched resins, wine lees powder and biodegradable resins with different terminal group types have good compatibility, increase their interfacial strength, and improve performance.

[0149] (4) Analysis of test results of different types of coupling agents and hyperbranched resins in the treatment of vinasse powder:

[0150] ① In Examples 2, 7 and 9, the hyperbranched resins are all carboxyl-terminated hyperbranched polyester Hyper C304. The difference is that the coupling agent used in Example 2 is KH560, the coupling agent used in Example 7 is NDZ-201, and the coupling agent used in Example 9 is KH550. It can be seen from the performance test results that the performance of Example 2 using KH560 and carboxyl-terminated hyperbranched polyester Hyper C304 is better than the other two. The amino group of the coupling agent KH550, the epoxy group of KH560, and the hydroxyl group of NDZ-201 react with the terminal carboxyl group of the hyperbranched polyester, respectively, wherein the amino group and the carboxyl group undergo an acid-base neutralization reaction, and the oxygen in the carboxyl group induces the electron absorption, so that the electronegativity of -OH oxygen in the carboxyl group is weakened, and the binding ability to H is weakened, and the carboxyl group and the amino group undergo a dehydration reaction; the carboxyl group, as a nucleophilic reagent, attacks the ring group to cause it to open its ring, and a nucleophilic addition reaction occurs, and the epoxy group and the carboxyl group form an ester bond, which has a strong chemical binding force. Since KH560 has a higher activation index, the reaction product is relatively stable, and it has a long alkyl chain, the modified vinasse powder has a slightly higher degree of crosslinking with the hyperbranched resin and the biodegradable resin, and the interface compatibility is better, so the modification effect is better than the biodegradable composite material obtained by modifying vinasse with KH550 and NDZ-201 in combination with the hyperbranched resin. This result is consistent with the conclusion obtained in ② of the above analysis (3). Similarly, the experimental conclusions obtained in Examples 5, 8 and 10 are consistent with the above. It can be concluded that KH560 is preferred among the three coupling agents.

[0151] ② The coupling agent in Examples 2, 5, 11 and 12 is KH560, except that the types of hyperbranched resins used are different. Example 2 uses carboxyl-terminated hyperbranched polyester Hyper C304, Example 5 uses carboxyl-terminated hyperbranched polyester Hyper C181, and Example 11 uses amino-terminated hyperbranched polyester Amine Functional Boltorn TMH40, Example 12 with terminal hydroxyl hyperbranched polyester Boltorn TM Regular H40. From the performance tests of these four examples, it can be seen that Example 2 using the carboxyl-terminated hyperbranched polyester Hyper C304 has the best performance. The same conclusion is also drawn from Examples 6, 9 and 10. This result is consistent with the conclusion drawn in ③ of the above analysis (3). It can be concluded that the hyperbranched resin is preferably the carboxyl-terminated hyperbranched polyester Hyper C304.

[0152] (5) Analysis of test results of Example 2 and Comparative Example 11:

[0153] In Example 2, the treatment order of the lees is first treated with a coupling agent and then with a hyperbranched resin; while the treatment order of the lees in Comparative Example 11 is opposite to that in Example 2, and it can be seen that the performance of Comparative Example 11 is significantly lower than that of Example 2. In the present invention, the treatment process of lees powder follows the principle of first treating with a coupling agent and then using a hyperbranched resin. This is based on the low viscosity and surface tension of the coupling agent and its strong wetting ability. It can be quickly spread on the surface of the lees powder, so that the surface of the lees powder is wetted by the silane coupling agent and evenly distributed on the surface of the treated lees powder, thereby improving the compatibility and dispersibility between the various component materials. When the surface of the lees powder is wetted, the groups on the coupling agent molecules diffuse to the surfaces with similar polarity. In Example 2, the alkoxy group at one end of the coupling agent KH560 is hydrolyzed to form a silanol group, which is oriented on the surface of the vinasse powder containing a large number of hydroxyl groups, and undergoes a hydrolysis and condensation reaction with the hydroxyl groups on the surface; the organic group is oriented on the surface of the hyperbranched resin and the biodegradable resin, and a chemical reaction occurs during the processing, thereby completing the coupling process of the vinasse powder, the hyperbranched resin and the biodegradable resin.

[0154] In summary, in the present invention, the decoupling agent molecules used have both organic groups that are pro-hyperbranched resin and biodegradable resin matrix materials, and groups that are pro-vinasse powder materials. Among them, the organic groups have a great influence on the performance of the product. Only when the organic groups can react with the corresponding hyperbranched resin and biodegradable resin matrix materials can the performance of the composite material be improved. The present invention selects three different types of coupling agents, namely, γ-glycidyloxypropyltrimethoxysilane (KH560) with an epoxy reaction group at the end, γ-aminopropyltriethoxysilane (KH-550) with an amino reaction group at the end, and isopropyl tri(dioctylpyrophosphate acyloxy) titanate (NDZ-201) with a hydroxyl reaction group at the end. These reaction groups can react chemically with the reaction groups carried by vinasse, hyperbranched resins with different end groups, and biodegradable resins. In the selection of hyperbranched resins, the present invention selects amino-terminated hyperbranched polyesters, carboxyl-terminated hyperbranched polyesters, hydroxyl-terminated hyperbranched polyesters and hyperbranched epoxy resins according to the different terminal reaction end groups of the hyperbranched resins, so as to match different types of coupling agents and biodegradable resins, and finally obtains a biodegradable green composite material with excellent performance, and at the same time, on the premise of meeting the product standards and performance, it is expected to increase the content of vinasse powder in the composite material, thereby accelerating the consumption of vinasse powder. Among the embodiments 1-22 of the present invention, embodiment 2 has the best comprehensive performance and is the optimal implementation scheme.

[0155] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing modified distiller's grains, characterized in that the steps include: (1) crushing and drying the vinasse, grinding and sieving to obtain vinasse powder; (2) adding a coupling agent to the vinasse powder, heating and stirring, and obtaining coupling agent treated vinasse; (3) Adding a hyperbranched resin to the coupling agent treated wine lees, heating and stirring for 5 to 45 minutes, and cooling to room temperature after the heating and stirring are completed to obtain modified wine lees.

2. The preparation method according to claim 1, characterized in that: The drying temperature in step (1) is 80-120° C.; the particle size of the vinasse powder is 100-2000 mesh.

3. The preparation method according to claim 1, characterized in that: The coupling agent in step (2) is selected from at least one of a silane coupling agent, an aluminate coupling agent and a titanate coupling agent; and the weight ratio of the vinasse powder to the coupling agent is 10:1 to 300:

1.

4. The preparation method according to claim 3, characterized in that: The silane coupling agent is at least one of γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane; and the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.

5. The preparation method according to claim 1, characterized in that: The hyperbranched resin in step (3) is selected from at least one of amino-terminated hyperbranched polyester, carboxyl-terminated hyperbranched polyester, hydroxyl-terminated hyperbranched polyester, hyperbranched epoxy resin, hydroxyl-terminated hyperbranched polyamide and amino-terminated hyperbranched polyamide; the weight ratio of vinasse powder to hyperbranched resin is 5:1 to 300:

1.

6. A green composite material made of fully biodegradable lees, characterized in that: The ingredients include 5-95wt% of biodegradable polyester, 0.1-15wt% of chain extender, 1-75wt% of modified wine lees, 0.1-15wt% of anti-hydrolysis agent, 0.1-5wt% of heat stabilizer and 0.1-7.5wt% of lubricant; the modified wine lees is prepared by any preparation method according to claim 1-5.

7. The green composite material of wine lees fully biodegradable according to claim 6, characterized in that: The biodegradable polyester is selected from at least one of polybutylene adipate / terephthalate copolyester, polylactic acid, polybutylene succinate, polybutylene succinate / adipate, polymethyl vinyl carbonate, polyglycolide, polyε-caprolactone, polyhydroxyalkanoate, polyhydroxybutyrate, polyhydroxyvalerate, and polyhydroxybutyrate / valerate; the chain extender is selected from at least one of epoxy compound chain extenders and styrene-methylacrylate copolymer chain extenders; the anti-hydrolysis agent is selected from at least one of carbodiimide compounds, isocyanate compounds, bisoxazoline compounds, and epoxy compounds; the heat stabilizer is selected from at least one of aromatic amine compounds, hindered phenol compounds, phosphite compounds, and thioester compounds; the lubricant is selected from at least one of long-chain carboxylic acids, amide waxes, carboxylates, carboxylates, and silicone resins.

8. The method for preparing the green composite material of vinasse biodegradable according to claim 6, characterized in that the steps include: The biodegradable polyester, chain extender, anti-hydrolysis agent, heat stabilizer and lubricant are mixed to obtain a biodegradable polyester material mixture; the biodegradable polyester material mixture is mixed with modified wine lees, and the mixture is fully dried to obtain a wine lees fully biodegradable green composite material.

9. Application of the fully biodegradable green composite material of distiller's grains as claimed in claim 6 as a material for film blowing, injection molding, casting, rotational molding, 3D printing, extrusion, coating, spinning, vacuum forming and molding.

Citation Information

Patent Citations

  • Wood-plastic material with distiller's grain as reinforcing phase, and manufacturing method thereof

    CN102746681A

  • Starch and polylactic acid composite material and preparation method thereof

    CN102863654A

  • Starch-base fully biodegradable resin with steady hydrophobic property and preparation method thereof

    CN104861210A

  • Distillers' grain polylactic acid full-degradable composite material, preparation method and application

    CN109575540A

  • Vinasse protein purification residue ultramicro filler, full-degradable composite material, preparation method and application of ultramicro filler and full-degradable composite material

    CN113563730A